Wheat middlings in roughage-based or limit-fed, high-concentrate diets for growing calves - Gerry L. Kuhl; R.H. Wessels; Dale A. Blasi; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1998)
A 101-day growing study was conducted to evaluate the growth performance of beef heifers fed wheat middlings in traditional full- fed, sorghum silage-based rations and in limit-fed, high-concentrate rations. Diets were formulated without wheat middlings or with wheat middlings replacing 33, 67, or 100% of rolled corn plus soybean meal. Daily gains decreased linearly (P<.01) with increasing levels of wheat middlings in the roughage-based diets because of lower feed intake (P<.10), but feed efficiency was not affected (P>.30). For the limit-fed diets, heifer daily gains decreased linearly (P<.01) as the proportion of wheat middlings in the diet increased, resulting in a linear reduction (P<.01) in feed efficiency. Wheat middlings can be utilized effectively as the predominant energy/protein source for growing cattle, though their nutritional and economic value, relative to corn and soybean meal, may be different for roughage-based and limit-fed diets.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Wheat middlings; Growing calves; Limit feeding; Sorghum silage